Tall al-Magass, Jordanien: Aseym-Projekt - Notroff, Jens; Siegel, Ulrike; Schmidt, Klaus (e-Forschungsberichte des DAI, 2023)
The Chalcolithic – Early Bronze Age tells of Hujayrat al-Ghuzlan and al-Magass are situated at the northern fringe of the modern town of Aqaba in southern Jordan. At both sites systematic archaeological research has taken place since excavations by Lutfi Khalil (University of Jordan) started in 1985. In 1998 the ASEYM project (Archaeological Survey and Excavation in the Yitim and Magaṣṣ Area) was established as a cooperation between the University of Jordan and the Orient Department of the DAI, continuing this previous research. The major focus of the field work in 2013 was on the documentation of the western section of Tall al-Magass, a deep profile being the result of road construction work in 1967.